A controlled experiment in maintenance comparing design patterns to simpler solutions. - Prechelt, L.
Software design patterns package proven solutions to recurring design problems in a form that simplifies reuse. We are seeking empirical evidence whether using design patterns is beneficial. In particular, one may prefer using a design pattern even if the actual design problem is simpler than that solved by the pattern, i.e., if not all of the functionality offered by the pattern is actually required. Our experiment investigates software maintenance scenarios that employ various design patterns and compares designs with patterns to simpler alternatives. The subjects were professional software engineers. In most of our nine maintenance tasks, we found positive effects from using a design pattern: either its inherent additional flexibility was achieved without requiring more maintenance time or maintenance time was reduced compared to the simpler alternative. In a few cases, we found negative effects: the alternative solution was less error-prone or required less maintenance time. Overall, we conclude that, unless there is a clear reason to prefer the simpler solution, it is probably wise to choose the flexibility provided by the design pattern because unexpected new requirements often appear. We identify several questions for future empirical research
Keywords: Decorator pattern; Controlled experiment; Design patterns; Design problem; Maintenance tasks; New requirements; Professional software engineers; Proven solutions; Recurring design problems; Reuse; Software design patterns; Software maintenance scenarios